2000
DOI: 10.1177/102831530000400102
|View full text |Cite
|
Sign up to set email alerts
|

Globalisation and Higher Education: Challenges for the 21st Century

Abstract: The article argues that the challenges facing higher education in the new millennium cannot be understood unless proper account is taken of the phenomenon of globalisation. Two points are emphasised. The first is that globalisation cannot simply be seen as a higher form of internationalisation; it is a much more turbulent phenomenon that not only transcends but ignores national boundaries. The second is that globalisation is one element within a larger shift from modernity to post-modernity, which involves not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
16

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 0 publications
0
73
0
16
Order By: Relevance
“…With a growing need for teamwork in the university teaching context (Scott 2000), it is important to explore whether well-researched models concerning team learning (Decuyper et al 2010; Van den Bossche et al 2011) can be applied to university teacher teams. As such, our research goal is to test our hypothesized relationships ( Fig.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…With a growing need for teamwork in the university teaching context (Scott 2000), it is important to explore whether well-researched models concerning team learning (Decuyper et al 2010; Van den Bossche et al 2011) can be applied to university teacher teams. As such, our research goal is to test our hypothesized relationships ( Fig.…”
Section: The Present Studymentioning
confidence: 99%
“…Traditionally, teaching at a university has been a highly individual and autonomous job (Van der Rijst 2009). Yet, demands from society require teachers to integrate their efforts to design multidisciplinary courses that provide students with a wide range of skills and knowledge (Scott 2000). The current study focuses on a university that had just initiated such an educational reform for all undergraduate study programs.…”
mentioning
confidence: 99%
“…Broadhead and Howard also locate the RAE as a form of punishment in higher education management 23 . 9 The audit of teaching and learning was also constructed by many of my informants as wasteful, stressful, over-bureaucratic, expensive and paradoxically guilty of diminishing teaching quality 24 . Other impact studies have also found it hard to relate the auditing of teaching and learning to its actual improvement.…”
Section: The Micropolitics Of Quality Professor Louise Morleymentioning
confidence: 99%
“…Enquanto a internacionalização valoriza as diferenças, hierarquias e hegemonias, a globalização valoriza o que é comum, subvertendo hierarquias e hegemonias (Scott, 2000). Essas diferentes concepções sobre globalização e internacionalização, de acordo com Maringe (2012), são reflexo não apenas da complexidade desses fenômenos, mas também refletem a divisão Norte-Sul, Oeste-Leste.…”
Section: Introductionunclassified
“…A segunda visão, denominada aqui de visão humanista, é concebida como um meio para construir uma mentalidade internacional entre alunos e professores, promover a consciência de um contexto internacional, preparar os egressos para atuar num mundo multicultural, incentivar estudantes e professores a aprenderem línguas estrangeiras e a trocar conhecimentos e experiências com parceiros de outros países (Knight, 2007;Scott, 2000;Shetty & Rudell, 2002).…”
Section: Introductionunclassified